Intrauterine Growth Restricted Rats Exercised at Pregnancy: Maternal–Fetal Repercussions. (August 2015) - Corvino, S. B.; Netto, A. O.; Sinzato, Y. K.; Campos, K. E.; Calderon, I. M. P.; Rudge, M. V. C.; Volpato, G. T.; Zambrano, E.; Damasceno, D. C.
To evaluate the effect of swimming in pregnant rats born with intrauterine growth restriction (IUGR) and their offspring, IUGR rats were obtained using the streptozotocin-induced severe diabetic (SD) rats. In this study, the nondiabetic parental generation presented 10 rats and diabetic parental generation presented 116 rats. Of these, the mated nondiabetic female rats were 10 and the number of diabetic rats was 45. In relation to term pregnancy, there were 10 animals in the nondiabetic group and 15 rats in the diabetic group. In the offspring of SD rats (IUGR group), 43 females were classified as small for pregnancy age, 19 rats were classified as appropriate for pregnancy age, and 0 female was classified as large for pregnancy age. The nondiabetic and SD pregnant rats generated offspring with appropriate (control [C]) and small (IUGR) weight for pregnancy age, respectively. At adult life, the C group was maintained as nonexercised C group and IUGR rats were distributed into 2 subgroups, namely, nonexercised (IUGR) and exercised (IUGRex). The rate of mated rats in the IUGR group was reduced compared to the C group. During pregnancy, the IUGR rats presented hyperinsulinemia, impaired reproductive outcomes, decreased body weight, hypertriglyceridemia, and hyperlactacidemia. The IUGRex presented reduced insulin and triglyceride levels. Thus, swimming improved lipid metabolism and increased insulin sensitivity. However, the offspring showed retarded growth, reinforcing the need to stimulate the exercise practice in women under supervision with different professional expertise to promote appropriate gestational conditions and improve perinatal outcomes.